Collaborative learning within critical mathematics education - Bulent Avci (Beta: Jurnal Tadris Matematika, 2020)
[English]: This article investigates ways in which collaborative learning in critical mathematics education can promote critical citizenship and democracy to counter neoliberal hegemony in education. Drawing on critical participatory action research in a U.S. high school classroom, the article argues that collaborative learning in critical mathematics education is a coherent alternative to neoliberal approaches to collaborative learning to promote justice based participatory democracy. Keywords: Critical mathematics education, Collaborative learning, Neoliberal pedagogy, Citizenship, Democracy [Bahasa]: Artikel ini menyelidiki bagaimana pembelajaran kolaboratif dalam pendidikan matematika kritis dapat mendorong terwujudnya demokrasi dan sikap warga negara yang kritis untuk melawan hegemoni neo-liberal dalam pendidikan. Merujuk pada penelitian tindakan kelas berbasis partisipasi kritis di kelas sekolah menengah atas di Amerika Serikat, artikel ini menunjukkan bahwa pembelajaran kolaboratif dalam pendidikan matematika kritis merupakan alternatif yang koheren terhadap pendekatan neo-liberal dalam pembelajaran kolaboratif untuk mendorong partisipasi demokratis berbasis keadilan. Kata kunci: Pendidikan matematika kritis, Pembelajaran kolaboratif, Pedagogi neo-liberal, Kewarganegaraan, Demokrasi